miR-133a-3p/TRPM4 axis improves palmitic acid induced vascular endothelial injury - Xue, Yadong; Tong, Tingting; Zhang, Yuyao; Huang, Haijun; Zhao, Ling; Lv, Hongzhao; Xiong, Lingzhao; Zhang, Kai; Han, Yuxuan; Fu, Yuyang; Wang, Yongzhen; Huo, Rong; et al. (Frontiers in Pharmacology, 2024)
Background: Vascular endothelial injury is a contributing factor to the development of atherosclerosis and the resulting cardiovascular diseases. One particular factor involved in endothelial cell apoptosis and atherosclerosis is palmitic acid (PA), which is a long-chain saturated fatty acid. In addition, transient receptor potential melastatin 4 (TRPM4), a non-selective cation channel, plays a significant role in endothelial dysfunction caused by various factors related to cardiovascular diseases. Despite this, the specific role and mechanisms of TRPM4 in atherosclerosis have not been fully understood. Methods: The protein and mRNA expressions of TRPM4, apoptosis - and inflammation-related factors were measured after PA treatment. The effect of TRPM4 knockout on the protein and mRNA expression of apoptosis and inflammation-related factors was detected. The changes of intracellular Ca2+, mitochondrial membrane potential, and reactive oxygen species were detected by Fluo-4 AM, JC-1, and DCFH-DA probes, respectively. To confirm the binding of miR-133a-3p to TRPM4, a dual luciferase reporter gene assay was conducted. Finally, the effects of miR-133a-3p and TRPM4 on intracellular Ca2+, mitochondrial membrane potential, and reactive oxygen species were examined. Results: Following PA treatment, the expression of TRPM4 increases, leading to calcium overload in endothelial cells. This calcium influx causes the assemblage of Bcl-2, resulting in the opening of mitochondrial calcium channels and mitochondrial damage, ultimately triggering apoptosis. Throughout this process, the mRNA and protein levels of IL-1β, ICAM-1, and VCAM1 significantly increase. Database screenings and luciferase assays have shown that miR-133a-3p preferentially binds to the 3′UTR region of TRPM4 mRNA, suppressing TRPM4 expression. During PA-induced endothelial injury, miR-133a-3p is significantly decreased, but overexpression of miR-133a-3p can attenuate the progression of endothelial injury. On the other hand, overexpression of TRPM4 counteracts the aforementioned changes. Conclusion: TRPM4 participates in vascular endothelial injury caused by PA. Therefore, targeting TRPM4 or miR-133a-3p may offer a novel pharmacological approach to preventing endothelial injury.